Revitalization of Manajemen Peningkatan Mutu Berbasis Madrasah (MPMBM) in Realizing Merdeka Belajar in Madrasas - Yose Rizal (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This paper examines the role of Manajemen Peningkatan Mutu Berbasis Madrasah in realizing Merdeka Belajar in the Madrasah environment. This study uses qualitative methods with data collection techniques through interviews. This is a field research conducted at Madrasah Aliyah Swasta Pondok Pesantren Modern Darul Hikmah Taman Pendidikan Islam Medan. This study found that Manajemen Peningkatan Mutu Berbasis Madrasah or MPMBM had a significant impact on madrasah principals in managing the BOS budget. Thus, the head of madrasah is able to make madrasa programs in realizing Merdeka Belajar at MAS PPMDH TPI Medan. There are three madrasa programs launched by the head of the Madrasah MAS PPMDH TPI Medan in allocating the 2020 BOS budget, which are Santri Membaca, Santri Digital, and Santri Siap Kuliah. The purpose of this research is to assist the ministry of education and culture in realizing Merdeka Belajar by using the BOS budget in the Madrasah.